MATHEMATICS LEARNING STRATEGIES FOR DEAF CHILDREN IN UNDERSTANDING STORY PROBLEMS - Fasya Zahira Shofa; Muhammad Rafael Al Farez; Fajar Yunia Dewi; Fika Nur Rahma; Noor Laila Sari; Yeni Rahma (PT. Jurnal Center Indonesia Publisher, 2026)
Mathematics learning plays an important role in developing logical thinking and problem-solving skills. However, for deaf students, understanding mathematical word problems remains a fairly complex challenge, mainly due to limitations in language and communication aspects. This study aims to examine the characteristics of the difficulties experienced by deaf students, analyze the implementation of the learning strategies used, and investigate their effectiveness in improving understanding of mathematical word problems. This research employs a qualitative approach using a literature study method. The findings indicate that the main difficulties lie in understanding the language used in the problems, identifying important information, and transforming it into mathematical models. Effective learning strategies tend to be visual, contextual, and communicative, supported by the use of interactive media. Nevertheless, the use of media alone is not sufficient without well-structured instructional strategies. These findings emphasize that the integration of adaptive learning strategies plays a more significant role in improving deaf students’ understanding of mathematical word problems.